Função citação como fator de recuperação de uma rede de assunto - Peixoto, Maria de Fátima Vieira (1985)
The scientific journal and its citation patterns provide a rich data source through Which, by using technics such as co-citation and bibliographic coupling, one can find the science structure reflected. In order to determine the nature of the representativeness of citations in relation to a specific area of knowledge-citations, the following hypothesis was presented regarding journals: one and only one entry point is the necessary and sufficient condition to have access to the citation network, representative of a specific area of scientific knowledge. From citations found in an article ( entry point) , a data base of 2.372 references was compiled in the 1960-1980 period. A second data base collected in three abstract journals, following the same criteria used previously, formed a series of 834 references used as the comparing unit to check the representativeness and extension of the area in relation to the first series. Comparing the two data bases, it was found a nucleus made of 82 coinciding articles . From the results obtained it was concluded that the hypothesis was confirmed, without specifying, however, if, in the whole or in part, since it was impossible to evaluate the extent that the information obtained through the citations corresponded to the "representative citation network" stated in its proposition. The degree of coincidences found between the two data bases was inconcludent, eventhough the 82 findings mentioned above are the clearest evidence of the access to a fraction of the citation network.